Teaching practice for pandemic times and the empowerment of audiovisual didactic sequences - Dias da Silva Rodrigues, Carina; dos Santos Sachete, Andréia; Rossi, Fábio (International Journal for Innovation Education and Research, 2021)
Closed gates and students away from classrooms consist of scenarios with thou- sands of schools in different countries, showing all the zeal we must have with teaching, which was opened wide by the indirect relationship between Education and Coronavirus. It is a frightening and troubling panorama, not only in health but also in teaching impacts. The learning process can and should hap- pen outside the classroom, and the pandemic accelerated this understanding. Technology support is fundamental for this to happen, eliminating any physical or geographical barrier of communication and interaction. However, the technological tools go further. Educational technologies are the leading solution to our situation and have the most significant potential for teaching children and young people. It is an opportunity to reframe Education and think of more effective ways to develop new children and young people. However, there is no ready recipe. Several frameworks for creating can guide audiovisual didactic sequences are not entirely descriptive in practice, applicability, or evaluation. Therefore, this work has its starting point the instructional design to supply this development, with other frameworks within its phases, allowing a better understanding of the objectives and greater ease in developing the instructional material. The results show that students well accept this new proposal.